Solar Light Radiometry Calibration Unit for a ScanPol Polarimeter of the Aerosol-UA Space Mission - Ivan Syniavskyi; Yevgen Oberemok; Vassyl Danylevsky; Yuriy Ivanov; Roman Osypenko; Mikhail Sosonkin; Gennadi Milinevsky (International Journal of Optics)
The Aerosol-UA space mission will study aerosol microphysical characteristics in the Earth’s atmosphere based on the multispectral scanning polarimeter (ScanPol) and imaging polarimeter (MSIP). Both polarimeters must be precisely calibrated on the ground and in orbit to provide correct measurements. This paper considers the results of developing an experimental device for the radiometric calibration of the ScanPol. We consider the calibration unit design and operation principle to form a luminous flux with unchanged or well-predicted characteristics in a specified direction. The construction of the radiometric calibration unit is based on a sun-illuminated reflective diffuser made from the white opal glass MS20. We evaluated the scattering and polarization characteristics of the diffuser in laboratory experiments at a wide range of wavelengths. The results suggest that the polarization properties of the diffuser are negligible. The diffuser scattering parameters are close to Lambertian for illuminance conditions, which is necessary for radiometric calibration. The calibration unit was manufactured and tested during field observations of solar radiation. The results will be used for its improvement, mainly to reduce the observed stray scattered radiation entering the telescopes of the ScanPol polarization state analyzer.